The behavioural, cognitive, and neural corollaries of blunted cardiovascular and cortisol reactions to acute psychological stress - Carroll, Douglas (Neurosci Biobehav Rev, 2017)
Recent research shows that blunted cardiovascular and cortisol reactions to acute psychological stress are associated with adverse behavioural and health outcomes: depression, obesity, bulimia, and addictions. These outcomes may reflect suboptimal functioning of the brain’s fronto-limbic systems that are needed to regulate motivated behaviour in the face of challenge. In support of this, brain imaging data demonstrate fronto-limbic hypoactivation during acute stress exposure. Those demonstrating blunted reactions also show impairments of motivation, including lower cognitive ability, more rapid cognitive decline, and poorer performance on motivation-dependent tests of lung function. Persons exhibiting blunted stress reactivity display well established temperament characteristics, including neuroticism and impulsivity, characteristic of various behavioural disorders. Notably, the outcomes related to blunted stress reactivity are similar to those that define Reward Deficiency Syndrome. Accordingly, some individuals may be characterised by a broad failure in cardiovascular and cortisol responding to both stress and reward, reflecting fronto-limbic dysregulation. Finally, we proffer a model of blunted stress reactivity, its antecedents and sequelae, and identify future research priorities.